Bazen Bir Puro Sadece Bir Purodur Leonardo Da Vinci’nin Dini Kimliği Üzerine Psikobiyografik Bir İnceleme - Kaplan, Hasan (Dinî araştırmalar, 2009)
Dan Brown’s bestseller book, The Da Vinci Code, already a motion picture, has captured popular interest all over the world; and has generated controversies about identity of Jesus and the authenticity of the Christian teachings. While religious implications of this “fact-mixed fiction" have been widely debated, the identity of Leonardo, whose shadow hovers over the entire controversy, seems to be still remaining elusive. Leonardo da Vinci is a mysterious figure whose name arouses curiosity and stirs controversy. Especially his religious identity is a matter of an ongoing debate. This is an essay in psychobiography aiming to shed some light on Leonardo’s puzzling personality. I will introduce an overlooked archival record about Leonardo’s travel to the East with the possibility of his conversion to Islamic faith that puts a new spin on this controversy and encourages our curiosity further. The details of this largely unknown (and somewhat ignored) journey are so rich that compel us to reconsider some claims of The Da Vinci Code, especially related to Leonardo's religious identity. Thus, guided by an Eriksonian insight, this study re-examines the life of Leonardo analyzing some psycho-social issues in his young adulthood years. It brings forth various biographical data that point to a tragic life of an out casted young man who was estranged from his community; a talented artist who was unappreciated and unemployed; and an all-sided genius in total crisis of identity, more specifically, crisis of faith